Causes and Consequences of Sexual Abuse and Resilience Factors in Housemaids Working in Addis Ababa: A Qualitative Inquiry - Ayenalem, Seblewongiel (Ethiopian Journal of Social Sciences, 2015)
This study explored the resilience of sexually abused female housemaids in Addis Ababa, Ethiopia. The study employed exploratory qualitative methods, using in-depth and key informant interviews to collect data. The participants were one broker, one counselor, and eight purposively selected housemaids who were young, single female migrants with impoverished family backgrounds.Â  Among the eight study participants, four experienced rape, one faced attempted rape, and the remaining three had their private body parts touched without their consent. Contexts that enhanced possibilities of sexual abuses, as expressed by respondents, include drinking of perpetuators, absence of wives from the home, lack of well-defined boundaries to the sector, and tricked with false promises. As a result, study participants faced emotional disturbance, distrust, hopelessness, job insecurity, unsafe abortion, unwanted pregnancy, and contracted HIV. The major strategies used by sexually abused housemaids to become resilient identified were normalizing the problem, disclosing, religious coping, personal values, and setting positive life goals. The study calls for service providers, professionals, policy makers, and legal agencies to recognize the issue of sexually abuse in housemaids as fertile ground for intervention research and practice.